2016
DOI: 10.18632/oncotarget.8713
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptome analysis identifies deregulated microRNA-transcription factor networks in lung adenocarcinoma

Abstract: Herein, we aimed at identifying global transcriptome microRNA (miRNA) changes and miRNA target genes in lung adenocarcinoma. Samples were selected as training (N = 24) and independent validation (N = 34) sets. Tissues were microdissected to obtain >90% tumor or normal lung cells, subjected to miRNA transcriptome sequencing and TaqMan quantitative PCR validation. We further integrated our data with published miRNA and mRNA expression datasets across 1,491 lung adenocarcinoma and 455 normal lung samples. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 79 publications
7
31
0
Order By: Relevance
“…25 Many research have showed that miR-1247-5p was downregulated in cancer tissues, and it act as a tumour inhibition factor. 16,[26][27][28] In accord with the above results, our study suggested that miR-1247-5p was downregulated in BC tissues relative to cancer free tissues, indicating that downregulation of miR-1247-5p expression was associated with carcinogenesis and cancer development of BC.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…25 Many research have showed that miR-1247-5p was downregulated in cancer tissues, and it act as a tumour inhibition factor. 16,[26][27][28] In accord with the above results, our study suggested that miR-1247-5p was downregulated in BC tissues relative to cancer free tissues, indicating that downregulation of miR-1247-5p expression was associated with carcinogenesis and cancer development of BC.…”
Section: Discussionsupporting
confidence: 85%
“…A systematic review showed that two candidate microRNAs (miR‐21 and miR‐210) were upregulated and six microRNAs (miR‐99a, miR‐139‐5p, miR‐145, miR‐195, miR‐205 and miR‐497) were downregulated in BC tissues comparing with normal tissues . Many research have showed that miR‐1247‐5p was downregulated in cancer tissues, and it act as a tumour inhibition factor . In accord with the above results, our study suggested that miR‐1247‐5p was downregulated in BC tissues relative to cancer free tissues, indicating that downregulation of miR‐1247‐5p expression was associated with carcinogenesis and cancer development of BC.…”
Section: Discussionsupporting
confidence: 85%
“…(22) In addition, as well as miR181-a and miR-181b, miR-181c, which has been shown to promote pancreatic cancer cell chemoresistance, (23) are aberrantly expressed in various cancers, including osteosarcoma and lung adenocarcinoma. (18,24) These findings raise the possibility that miR-181b and miR-181c have a similar function to miR-181a in HCC cells. In addition, Ji et al (16) indicate that all members of miR-181s are associated with HCC cells with features of hepatic cancer stem cells, suggesting that HepG2 cells, which have mature features of HCC cells, express lower levels of miR-181s.…”
Section: Discussionmentioning
confidence: 92%
“…We showed that miR‐181a directly represses expression of RASSF1 in HCC cells, which is consistent with a recent report that miR‐181a and miR‐181b are highly expressed in acute promyelocytic leukemia and downregulate RASSF1 expression . In addition, as well as miR181‐a and miR‐181b, miR‐181c, which has been shown to promote pancreatic cancer cell chemoresistance, are aberrantly expressed in various cancers, including osteosarcoma and lung adenocarcinoma . These findings raise the possibility that miR‐181b and miR‐181c have a similar function to miR‐181a in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 miR-421 expression was also screened to be higher in lung adenocarcinoma tissues in comparison to adjacent normal tissues. 10 miR-421, located at the Xq13.2 region of the X chromosome, is closely related to the checkpoint changes of S-phase cell cycle and increased sensitivity to ionizing radiation through its ectopic expression. 11 miR-421 has been reported to negatively target caspase-3 at the posttranscriptional level, as well as to regulate Bcl-2-Associated X protein (Bax) and Bcell lymphoma-2 (Bcl-2), ultimately highlighting its role as a tumor promoter in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%